THE MODERATION ROLE OF INVENTORY MANAGEMENT INFORMATION SYSTEM IN HUMAN RESOURCE COMPETENCE ON THE QUALITY OF GOVERNMENT FINANCIAL REPORTS: EVIDENCE FROM 40 REGIONAL GOVERNMENT AGENCIES IN CENTRAL SULAWESI PROVINCE - Ahmad Azhami; Rahma Masdar; Muhammad Din; Betty; Muhammad Ikbal Abdullah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The importance of measuring the quality of government financial reports by reviewing human resource competencies and the use of inventory management technology in moderating their relationship is the objective of this study. By distributing questionnaires to 40 regional agencies in the Central Sulawesi Provincial Government, to parties directly involved in the operation of financial reports and inventory systems, through purposive sampling, a total of 114 research respondents were tested. The findings reveal that, directly, the relationship between human resource competence and the quality of financial reports is crucial, so that the ability, knowledge, and understanding of reporting preparation are very necessary, with a significant value of 69%. In addition, the use of the Central Sulawesi Provincial Government's inventory management information system was able to strengthen the relationship between the two, although it had a value of less than 15%, which was lower than the direct relationship. Thus, these findings emphasize the need to improve the quality of the apparatus in utilizing information technology to provide quality information efficiently, effectively, and economically as a form of government accountability and transparency to the public.